2020
DOI: 10.1177/2398212820925580
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal–hippocampal interaction during the encoding of new memories

Abstract: The hippocampus rapidly forms associations among ongoing events as they unfold and later instructs the gradual stabilisation of their memory traces in the neocortex. Although this two-stage model of memory consolidation has gained substantial empirical support, parallel evidence from rodent studies suggests that the neocortex, in particular the medial prefrontal cortex, might work in concert with the hippocampus during the encoding of new experiences. This opinion article first summarises findings from behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 151 publications
(166 reference statements)
2
23
0
1
Order By: Relevance
“…Theories posit that these pattern recognition and integration processes allow for building an internal model of the world, in other words, prior knowledge or schema (Marr, 1971;McClelland et al, 1995;Winocur et al, 2010;Sekeres et al, 2018). The present finding raises the possibility that the mPFC might also play a similar role at the time of memory encoding (Takehara-Nishiuchi, 2020b). Rapid firing generation from the CS1 to the CS2 alludes to the integration of stimulus information with the same biological significance over time, which enables the mPFC to detect, in real time, relevant contents of a new experience.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Theories posit that these pattern recognition and integration processes allow for building an internal model of the world, in other words, prior knowledge or schema (Marr, 1971;McClelland et al, 1995;Winocur et al, 2010;Sekeres et al, 2018). The present finding raises the possibility that the mPFC might also play a similar role at the time of memory encoding (Takehara-Nishiuchi, 2020b). Rapid firing generation from the CS1 to the CS2 alludes to the integration of stimulus information with the same biological significance over time, which enables the mPFC to detect, in real time, relevant contents of a new experience.…”
Section: Discussionmentioning
confidence: 56%
“…Parallel studies also showed that by enhancing the activity of mPFC neurons during training, it is possible to facilitate the acquisition of hippocampusdependent memories (Benn et al, 2016;Volle et al, 2016;Jarovi et al, 2018;Shibano et al, 2020). These observations, along with earlier findings of impaired hippocampus-dependent memories with disrupted mPFC (Hannesson et al, 2004;Takehara-Nishiuchi et al, 2005;Zhao et al, 2005;Barker and Warburton, 2008;Gilmartin and Helmstetter, 2010;Devito and Eichenbaum, 2011;Gilmartin et al, 2013;Bero et al, 2014), led us to hypothesize that the mPFC may work with, but not follows, the hippocampus to form new memories (Takehara-Nishiuchi, 2020b).…”
Section: Introductionmentioning
confidence: 75%
“…Theories posit that these pattern recognition and integration processes allow for building an internal model of the world, in other words, prior knowledge or schema (Marr, 1971;McClelland et al, 1995;Winocur et al, 2010;Sekeres et al, 2018). The present finding raises the possibility that the mPFC might also play a similar role at the time of memory encoding (Takehara-Nishiuchi, 2020b). Rapid firing generation from the CS1 to the CS2 alludes to the integration of stimulus information with the same biological significance over time, which enables the mPFC to detect, in real time, relevant (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 52%
“…The copyright holder for this preprint this version posted August 27, 2020. ; https://doi.org/10.1101/2020.08.26.269035 doi: bioRxiv preprint mPFC neurons during training, it is possible to facilitate the acquisition of hippocampusdependent memories (Benn et al, 2016;Volle et al, 2016;Jarovi et al, 2018;Shibano et al, 2020). These observations, along with earlier findings of impaired hippocampus-dependent memories with disrupted mPFC (Hannesson et al, 2004;Takehara-Nishiuchi et al, 2005;Zhao et al, 2005;Barker and Warburton, 2008;Gilmartin and Helmstetter, 2010;Devito and Eichenbaum, 2011;Gilmartin et al, 2013;Bero et al, 2014), led us to hypothesize that the mPFC may work with, but not follows, the hippocampus to form new memories (Takehara-Nishiuchi, 2020b).…”
Section: Introductionmentioning
confidence: 78%
“…Action selection and behavioral flexibility in response to changing circumstances are largely mediated by cortico-striatal-thalamic circuits 44 . Moreover, gaps in memory encoding or consolidation might be associated with reduced function of prefrontal and hippocampal areas 45,46 , deficits in inhibitory control with fronto-striatal regions 1,37 , and impairments in working memory and behavioral flexibility mainly with prefrontal regions 1,6 – all brain regions that have been shown to be affected by AIE exposure 6 . Thus, we hypothesized that behavioral deficits would be associated with altered functional connectivity among fronto-limbic regions in AIE-exposed animals.…”
Section: Discussionmentioning
confidence: 99%